2012
DOI: 10.1186/1471-244x-12-66
|View full text |Cite
|
Sign up to set email alerts
|

Internet-delivered attention bias modification training in individuals with social anxiety disorder - a double blind randomized controlled trial

Abstract: BackgroundComputerized cognitive bias modification for social anxiety disorder has in several well conducted trials shown great promise with as many as 72% no longer fulfilling diagnostic criteria after a 4 week training program. To test if the same program can be transferred from a clinical setting to an internet delivered home based treatment the authors conducted a randomized, double-blind placebo-controlled trial.MethodsAfter a diagnostic interview 79 participants were randomized to one of two attention tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
149
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(168 citation statements)
references
References 56 publications
12
149
1
2
Order By: Relevance
“…Although the applied training procedure closely resembled procedures that have effectively implemented ABM (Amir et al, 2008;Van Bockstaele et al, 2011), we did not find changes in attention bias at the training condition level in response to training toward negative, positive, or away from negative with various stimulus materials (i.e., emotional scenes, words, facial expressions) and stimulus presentation durations (500ms, 750ms, 1000ms). Thus, the present findings add to recent research that did not replicate successful ABM delivery (e.g., Boettcher et al, 2013;Carlbring et al, 2012;Rapee et al, 2013).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although the applied training procedure closely resembled procedures that have effectively implemented ABM (Amir et al, 2008;Van Bockstaele et al, 2011), we did not find changes in attention bias at the training condition level in response to training toward negative, positive, or away from negative with various stimulus materials (i.e., emotional scenes, words, facial expressions) and stimulus presentation durations (500ms, 750ms, 1000ms). Thus, the present findings add to recent research that did not replicate successful ABM delivery (e.g., Boettcher et al, 2013;Carlbring et al, 2012;Rapee et al, 2013).…”
Section: Discussionsupporting
confidence: 76%
“…For depression, meta-analytic evidence suggests no effects of ABM on depressive symptomatology, but note that there is little research testing ABM in depressed samples (see Mogoase et al, 2014). While several recent ABM studies did not produce clinically significant changes (Boettcher, Andersson, Carlbring, & Group, 2013;Carlbring et al, 2012;Julian, Beard, Schmidt, Powers, & Smits, 2012;Neubauer et al, 2013;Rapee et al, 2013), such failures might be due to failures of ABM to change attentional bias at the training condition (group) level (Clarke, Notebaert, & MacLeod, 2014). Yet, there is large variability among trainees in attention bias acquisition following ABM delivery and such individual differences may predict anxiety levels (e.g., Clarke, Chen, & Guastella, 2012;Clarke, MacLeod, & Shirazee, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] In the other nine studies, there were differences between groups, and AB for threat was reduced in the avoid groups, when compared with the control group.…”
Section: Introductionmentioning
confidence: 92%
“…However, several studies that compared avoid and control groups [21][22][23]52 found no differences between groups after training. One possible explanation for this phenomenon might be that avoidance training demands a greater cognitive effort, as it goes against the trend preferred by participants, whereas training to attend reinforces this trend and does not demand any special cognitive effort.…”
Section: Eating Behaviormentioning
confidence: 99%
“…Two meta-analyses have demonstrated small to medium effect sizes of ABM for anxiety disorders (Hakamata et al, 2010;Hallion & Ruscio, 2011). However, the promising findings found with ABM conducted in a laboratory setting have not been replicated when the same treatment has been delivered via the internet (Boettcher, Berger, & Renneberg, 2011;Carlbring et al, 2012;Neubauer et al, 2013). It is possible that ABM only works for individuals showing an attentional bias before treatment initiation and the context where ABM is delivered may also be important (MacLeod & Grafton, 2016;Price et al, 2016).…”
Section: Attention Bias Modificationmentioning
confidence: 99%